Circulating vitamin D concentration and risk of seven cancers: a Mendelian randomization study - Dimitrakopoulou, V; Tsilidis, K; Haycock, P; Key, T; Travis, R (BMJ Publishing Group, 2017)
Objective To determine if circulating concentrations of vitamin D are causally associated with risk of cancer. There is debate on whether vitamin D status is a cause of disease or just a correlate marker of overall health. Evidence from in-vitro and animal model studies supports an anti-neoplastic role of vitamin D, but epidemiological studies and randomized controlled trials have yielded mixed results. Design To overcome potential limitations in epidemiological studies and randomized controlled trials, a Mendelian randomization (MR) approach was used. Participants and Setting A total of 70,563 cancer cases and 84,418 controls were used from large genetic epidemiology networks, which consisted of 22,898 cases of prostate cancer, 15,748 cases of breast cancer, 12,537 cases of lung cancer, 11,488 cases of colorectal cancer, 4,369 cases of ovarian cancer, 1,896 cases of pancreatic cancer and 1,627 cases of neuroblastoma. Exposures Four vitamin D associated single nucleotide polymorphisms (SNPs: rs2282679, rs10741657, rs12785878 and rs6013897) were used to define a multi-SNP score for circulating 25-hydroxyvitamin D (25(OH)D) concentrations. Main outcomes and measures The primary outcomes were the risk of incident colorectal, breast, prostate, ovarian, lung and pancreatic cancer, and neuroblastoma, which was evaluated using an inverse-variance weighted average of the SNP-specific associations and a likelihood-based approach. Secondary outcomes based on cancer subtypes by sex, anatomic location, stage and histology were also examined. Results There was little evidence that the multi-SNP score of 25(OH)D was associated with risk of any of the seven cancers or their subtypes. Specifically, the odds ratios per 25 nmol/L increase in genetically-determined 25(OH)D concentrations were 0.92 (95% CI, 0.76-1.10) for colorectal cancer, 1.05 (95% CI, 0.89-1.24) for breast cancer, 0.89 (95% CI, 0.77-1.02) for prostate cancer, and 1.03 (95% CI, 0.87-1.23) for lung cancer. The results were consistent with the two different analytic approaches, and the study was powered to detect relative effect sizes of moderate magnitude (e.g., 1.20-1.50) per 25 nmol/L decrease in 25(OH)D for most primary cancer outcomes. The MR assumptions did not appear to be violated. Conclusions Our results provide little evidence of a linear causal association between circulating vitamin D concentration and risk of colorectal, breast, prostate, ovarian, lung and pancreatic cancer, and neuroblastoma, but we cannot rule out existence of causal clinically relevant effects of low magnitude. These results, in combination with previous literature, provide evidence that population-wide screening for vitamin D deficiency and subsequent widespread vitamin D supplementation should not be recommended at this time as a primary cancer prevention strategy.